Self Reported Dental Clinic Visits of Adolescents in Nigeria Rural Communities (Update Dental College Journal, 2025)
Background: The health care utilization of a rural or urban population is dependent on their health seeking behaviour, which are activities carried out to maintain good health, to prevent poor health or any departure from a good state of health.Objective:  To determine the self-reported dental clinic visits of adolescents in south eastern Nigerian rural areas.Methodology: A secondary data analysis was done. The primary data was obtained from a cross-sectional study that recruited 272 children from a rural public technical college and three public secondary schools selected in Nkanu–West and Udi local Government Area of Enugu State respectively. Socio-demographic data (age, sex, socio-economic status)  was obtained using semi-structured questionnaire. Information on dental clinic visit was obtained by self- administered questionnaire. Data were analysed using SPSS Version 25 .P values < 0.05 were accepted as being statistically significant. Frequency distribution and standard deviation were calculated. Test of association between gender, age and socio-economic status with dental clinic visits were conducted using Fisher exact test.Results: A total of 129 (47.4%) males and 143 (52.6%) females participated in this study. The prevalence of dental clinic visits was 1.8%. Dental clinic visit was higher among females than males. There was no statistically significant association between sex (P = 0.37), age (P= 0.40) and dental clinic visit. The association between socio-economic status and dental clinic visit was statistically significant. P